Heme oxygenase-1 affects cytochrome P450 function through the formation of heteromeric complexes: Interactions between CYP1A2 and heme oxygenase-1 - Connick, J. Patrick (J Biol Chem, 2020)
Heme oxygenase 1 (HO-1) and the cytochromes P450 (P450s) are endoplasmic reticulum–bound enzymes that rely on the same protein, NADPH-cytochrome P450 reductase (POR), to provide the electrons necessary for substrate metabolism. Although the HO-1 and P450 systems are interconnected owing to their common electron donor, they generally have been studied separately. As the expressions of both HO-1 and P450s are affected by xenobiotic exposure, changes in HO-1 expression can potentially affect P450 function and, conversely, changes in P450 expression can influence HO-1. The goal of this study was to examine interactions between the P450 and HO-1 systems. Using bioluminescence resonance energy transfer (BRET), HO-1 formed HO-1•P450 complexes with CYP1A2, CYP1A1, and CYP2D6, but not all P450s. Studies then focused on the HO-1–CYP1A2 interaction. CYP1A2 formed a physical complex with HO-1 that was stable in the presence of POR. As expected, both HO-1 and CYP1A2 formed BRET-detectable complexes with POR. The POR•CYP1A2 complex was readily disrupted by the addition of HO-1, whereas the POR•HO-1 complex was not significantly affected by the addition of CYP1A2. Interestingly, enzyme activities did not follow this pattern. BRET data suggested substantial inhibition of CYP1A2-mediated 7-ethoxyresorufin de-ethylation in the presence of HO-1, whereas its activity was actually stimulated at subsaturating POR. In contrast, HO-1–mediated heme metabolism was inhibited at subsaturating POR. These results indicate that HO-1 and CYP1A2 form a stable complex and have mutual effects on the catalytic behavior of both proteins that cannot be explained by a simple competition for POR.